Conflito socioambiental e o papel dos conselhos gestores: a experiência de São Sebastião, São Paulo - Pascalicchio, Daniel Eleuterio (2009)
The number of public policy councilis in Brazil grew during enhaced by the constitution of 1988. Brazilian municipalities had the federal responsability enlarged especially does concerned to urban devolopment and environment and urban planning theories melt down contribute to the development of the city with a case study of São Sebastião, at the north coast of São Paulo State, focusing on the Council of Environment and Urban Development (Conselho MUnicipal de Meio Ambiente e DEsenvolvimento Urbano) as a place of planning, conflict an negoatiation of local issues. The discussions and conclusions, from the point view of the democratic theory, concerns on aspects of participation and deliberation as the central dilemmas of the participatory arenas, as a result the work points out the limits and opportunities of this council in managing local public policies.